2016
DOI: 10.1002/art.39653
|View full text |Cite
|
Sign up to set email alerts
|

Changes in White Matter Microstructure Suggest an Inflammatory Origin of Neuropsychiatric Systemic Lupus Erythematosus

Abstract: Objective. To assess white matter (WM) and gray matter (GM) magnetization transfer ratio histogram peak heights (MTR-HPHs) in different subsets of patients with neuropsychiatric systemic lupus erythematosus (NPSLE) who have unremarkable findings on 3T magnetic resonance imaging of the brain and to evaluate whether these values could be used to highlight different clinically suspected underlying pathogenic processes or identify the clinical NPSLE status or whether they could be associated with a specific NPSLE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…A decrease in bound molecules (e.g., due to demyelination) or an increase in unbound molecules (e.g., due to edema) can diminish the energy transfer or MTR. Decreased whole‐brain MTR, even in the absence of other structural MRI changes, has been reported in SLE . It is reversible and most likely reflects parenchymal edema .…”
Section: Current Status Of Npslementioning
confidence: 93%
“…A decrease in bound molecules (e.g., due to demyelination) or an increase in unbound molecules (e.g., due to edema) can diminish the energy transfer or MTR. Decreased whole‐brain MTR, even in the absence of other structural MRI changes, has been reported in SLE . It is reversible and most likely reflects parenchymal edema .…”
Section: Current Status Of Npslementioning
confidence: 93%
“…Evaluations included in the multidisciplinary assessment and MRI-scanning protocol are described elsewhere. 2,16 The multidisciplinary team met every two weeks to discuss the patients and evaluate the complementary assessments. The following aspects were taken into account: (a) objective confirmation of symptoms assessed to standard of care of the appropriate medical specialty; (b) attribution to SLE or other aetiology.…”
Section: Methodsmentioning
confidence: 99%
“…They are, however, sensitive to diffuse, global effects, and successive studies have shown the sensitivity of MTR histograms to a variety of disease related clinical factors (6973), including to the presence of specific antibodies. It was recently shown that white matter MTR histogram peak heights (HPH) were significantly lower in inflammatory NP-SLE patients than in NP-SLE patients diagnosed as ischemic, as well as than SLE patients with no NP complaints and healthy controls (74). The mechanism by which the MTR is decreased in NP-SLE is not clear, but its reversibility upon successful treatment suggests intracellular edema and gliosis as the associated pathomechanisms (75).…”
Section: The Challenges Of Establishing a Neuroimaging Biomarker In Nmentioning
confidence: 99%